Opportunities and Challenges: Hepatitis C Testing and Treatment Access Experiences Among People in Methadone and Buprenorphine Treatment During COVID-19, Arizona, 2021 - Beth E. Meyerson, PhD; Danielle M. Russell, MS; Missy Downer, BS; Amirah Alfar; Irene Garnett, MLIS; John Lowther; Rebecca Lutz; Arlene Mahoney, BSW; Julie Moore; Greg Nuñez; Savannah Samorano, AA; Benjamin R. Brady, DrPH; et al. (Elsevier, 2023)
Introduction: The purpose of this study was to characterize hepatitis C virus screening and treatment access experiences among people in treatment for opioid use disorder in Arizona during COVID-19. Methods: Arizonans receiving treatment for opioid use disorder from methadone clinics and buprenorphine providers during COVID-19 were interviewed about hepatitis C virus testing, curative treatment, and knowledge about screening recommendations. Interviews were conducted with 121 people from August 4, 2021 to October 10, 2021. Qualitative data were coded using the categories of hepatitis C virus testing, knowledge of screening recommendations, diagnosis, and experiences seeking curative treatment. Data were also quantitated for bivariate testing with outcome variables of last hepatitis C virus test, diagnosis, and curative treatment process. Findings were arrayed along an adapted hepatitis C virus cascade framework to inform program and policy improvements. Results: Just over half of the sample reported ever having tested for hepatitis C virus (51.2%, n=62) and of this group, 58.1% were tested in the past 12 months. Among those who were ever tested, 54.8% reported a hepatitis C virus diagnosis and 16.1% reported either being in treatment or having been declared cured of the hepatitis C virus. Among those who were diagnosed with hepatitis C, 14.7% indicated that they unsuccessfully tried to access curative treatment and would not attempt to again. Reasons cited for not accessing or receiving curative treatment included beliefs about treatment safety, barriers created by access requirements, natural resolution of the infection, and issues with healthcare coverage and authorization. Conclusions: Structural barriers continue to prevent curative hepatitis C virus treatment access. Given that methadone and buprenorphine treatment providers serve patients who are largely undiagnosed or treated for hepatitis C virus, opportunities exist for them to screen their patients regularly and provide support for and/or navigation to hepatitis C virus curative treatment.